PELAKSANAAN STANDAR PELAYANAN KEFARMASIAN DI APOTEK KOTA PALU - Diana, Khusnul; Tandah, Muhamad Rinaldhi; Basuki, Muhamad (Fakultas Farmasi UMI, 2019)
Â The standard of pharmaceutical service is a benchmark or guideline for parmacist in carrying out pharmaceutical service in pharmacy facilities, one of them is pharmacy, in order to realize optimal health in the community. This study aims to describe the implementation of standard pharmaceutical services at the pharmacy in Palu city. This study was an observational study with descriptive qualitative data, data collection was cross sectional with the total number of samples are 56 respondents pharmacists / pharmacy in Palu city. Data was collected using questionnaire sheets distributed to respondents. From the results of the study, the standard clinical pharmacy services performed by pharmacists in the form of prescription study activities (61.6%), dispensing (36.9%), counseling (52.5%). The standard of drug management, medical devices and medical disposable carried out by pharmacist (54.3%). Clinical service standards that were not implemented at the pharmacy in the form of drug information services (62.1%), monitoring drug therapy (78.3%) and monitoring drug side effects (89.9%).